Die gebruik van innoverende intervensie met die adolessente kind van die alkoholis - Venter, N; Kruger, SP (Social Work/Maatskaplike Werk, 2002)
The research described in the article links the classical adaptive behaviour of children of alcoholics with possible underlying emotional reactions. As a result of these intensive feelings adolescents are at risk of developing maladaptive behaviour which has the potential to affect their social adjustment negatively. Intra- and interrelationships are negatively affected and this needs to be combated through the development of a positive self-image as well as effective life skills. Social work must intervene proactively. Due to the typical feelings and emotional needs of adolescents, this is best done through peer group intervention with the focus on self-help . Sharing of feelings and experiences and the incorporation of relevant knowledge builds up resilience against the possible negative effect of parental alcoholism. Practical strategies and activities to be utilised during peer group intervention are discussed. The therapeutic value of art therapy, psycho-drama, sculpting and biblio-therapy, amongst others, is described .